Cognitive Agents for Virtual Environments First International Workshop, CAVE 2012, Held at AAMAS 2012, Valencia, Spain, June 4, 2012, Revised Selected Papers - Dignum, Frank; Brom, Cyril; Hindriks, Koen.; Beer, Martin; Richards, Deborah; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed post-proceedings of the First International Workshop on Cognitive Agents for Virtual Environments, CAVE 2012, held at AAMAS 2012, in Valencia, Spain, in June 2012. The 10 full papers presented were thoroughly reviewed and selected from 14 submissions. In addition one invited high quality contribution has been included. The papers are organized in the following topical sections: coupling agents and game engines; using games with agents for education; visualization and simulation; and evaluating games with agents.
Coupling Agents and Game Engines -- HLA Proxy: Towards Connecting Agents to Virtual Environments by Means of High Level Architecture (HLA -- Decoupling Cognitive Agents and Virtual Environments -- Agent Communication for Believable Human-Like Interactions between Virtual Characters -- Using Games with Agents for Education -- Using Agents in Virtual Environments to Assist Controllers to Manage Multiple Assets -- A Collaborative Agent Architecture with Human-Agent Communication Model -- Improving Agent Team Performance through Helper Agents -- Visualisation and Simulation -- Visualisation on Demand for Agent-Based Simulation -- A Cognitive Module in a Decision-Making Architecture for Agents in Urban Simulations -- Evaluating Games with Agents -- Improving Situation Awareness in Intelligent Virtual Agents -- Generating Corpora of Activities of Daily Living and towards Measuring the Corpora$1 (Bs -- Does High-Level Behavior Specification Tool Make Production of Virtual Agent Behaviors Better?.s
Keywords: Computer science; Artificial intelligence; Education; Computer Science; Artificial Intelligence (incl. Robotics).; Personal Computing; Computers and Education